Reconstruction of Islamic Religious Education Curriculum in Building Moderate Student Character in the Digital Era - Mahmud Hafiz; Farih F. Mirza; Wakib Kurniawan (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
Islamic Religious Education (PAI) plays an important role in the formation of students' moderate character, especially in the digital era that is filled with various information and external influences. This study aims to analyse the challenges and opportunities faced in the implementation of the Islamic Education curriculum in schools, as well as to design a curriculum reconstruction model that can build students' moderate character through the use of digital technology. The method used in this research is a qualitative approach with content analysis of the existing PAI curriculum, as well as interviews with educators and curriculum experts. The results showed that the current PAI curriculum has not fully accommodated technological developments and has not been optimal in shaping inclusive moderate character. Therefore, a curriculum reconstruction is needed that not only integrates technology as a medium of learning, but also instils religious moderation values that are adaptive to the dynamics of the times. The reconstruction model proposed in this research aims to produce a curriculum that is more responsive and relevant for students in the digital era.